Neurosteroid-like Inhibitors of N-Methyl-d-aspartate Receptor: Substituted 2-Sulfates and 2-Hemisuccinates of Perhydrophenanthrene - Slavikova, Barbora; Chodounska, Hana; Nekardova, Michaela; Vyklicky, Vojtech; Ladislav, Marek; Hubalkova, Pavla; Krausova, Barbora; Vyklicky, Ladislav; Kudova, Eva (Journal of medicinal chemistry, 2016)
N-Methyl-d-aspartate receptors (NMDARs) display a critical role in various diseases of the central nervous system. The activity of NMDARs can be modulated by neurosteroids. Herein, we report a structure-activity relationship study for perhydrophenanthrene analogues possessing a framework that mimics the steroidal ring system. This study comprises the design, synthesis, and assessment of the biological activity of a library of perhydrophenanthrene 2-sulfates and 2-hemisuccinates (1-10). Their ability to modulate NMDAR-induced currents was tested on recombinant GluN1/GluN2B receptors. Our results demonstrate that such structural optimization leads to compounds that are inhibitors of NMDARs. Notably, compound 9 (IC50 = 15.6 μM) was assessed as a more potent inhibitor of NMDAR-induced currents than the known endogenous neurosteroid, pregnanolone sulfate (IC50 = 24.6 μM).
Keywords: HEK293 buňky; Structure-Activity Relationship; Thermodynamics; molekulární struktura; Molecular Structure; vztah mezi dávkou a účinkem léčiva; kvantová teorie; HEK293 Cells; sírany; Succinates; vztahy mezi strukturou a aktivitou; termodynamika; Phenanthrenes; Sulfates; lidé; Humans; sukcináty; Quantum Theory; Dose-Response Relationship, Drug; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; fenantreny